IMPLEMENTASI METODE QUANTUM TEACHING TERHADAP PENINGKATAN HASIL BELAJAR MATEMATIKA PADA SISWA SEKOLAH MENENGAH PERTAMA - Tuty Novelindah Purba (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
In general, this study was to determine the application of the quantum teaching-learning method with the discussion method in improving mathematics learning outcomes for seventh-grade students of SMP Negeri 2 Dolok Pardamean, Simalungun Regency. This study used experimental research on grade VII students of SMP Negeri 2 Dolok Pardamean, Simalungun Regency. The research was conducted by taking samples from two classes, namely the experimental class (15 students per class) and the control class (15 students per class). The sample categories were taken from two of four parallel categories that were determined randomly (random category samples). The tool used in this study was a testing technique in the form of empirically verified paper questions. Data analysis used the t-test, first testing for normality and homogeneity. Based on the results of data processing, it was known that the application of the quantum teaching-learning model with the discussion method had a significant effect on increasing mathematics learning outcomes obtained.